Cell senescence: basic mechanisms and the need for computational networks in vascular ageing. Issue 8 (3rd November 2020) - Regnault, Véronique; Challande, Pascal; Pinet, Florence; Li, Zhenlin; Lacolley, Patrick
Abstract: This review seeks to provide an update of the mechanisms of vascular cell senescence, from newly identified molecules to arterial ageing phenotypes, and finally to present a computational approach to connect these selected proteins in biological networks. We will discuss current key signalling and gene expression pathways by which these focus proteins and networks drive normal and accelerated vascular ageing. We also review the possibility that senolytic drugs, designed to restore normal cell differentiation and function, could effectively treat multiple age-related vascular diseases. Finally, we discuss how cell senescence is both a cause and a consequence of vascular ageing because of the possible feedback controls between identified networks. Graphical Abstract: